UPAYA MENERAPKAN SUPERVISI AKADEMIK DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SD NEGERI 015/VIII SUNGAI BENGKAL - WALUYO WALUYO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to implement academic supervision in improving the pedagogical competence of teachers at SD Negeri 015/VIII Sungai Bengkal, Tebo Ilir, Tebo Jambi Province in the odd semester of the 2015/2016 academic year. This research method is PTS (School Action Research). Activities in this research consist of stages of action planning, action implementation, observation, and reflection. Data collection techniques using class observation techniques. The observation instrument used was a teacher ability assessment tool (APKG) in the form of: 1) an instrument for assessing the ability of teachers in developing a syllabus, 2) an instrument for assessing the ability of teachers in preparing lesson plans, 3) an instrument for assessing the ability of teachers in the implementation of learning. Analysis of the data used is a comparative descriptive analysis technique. The quantitative data obtained are described in the form of words or explanations. Furthermore, data comparisons are carried out to ensure whether there is an increase in the ability of teachers in preparing lesson plans, increasing the ability of teachers in implementation. The results showed that academic supervision could: a) increase the competence of class VI teachers in developing the syllabus at SD Negeri 015/VIII Sungai Bengkal by 41%. b) increasing the ability of class VI teachers in preparing lesson plans at SD Negeri 015/VIII Sungai Bengkal by 39%. c) increase the ability of class VI teachers in carrying out learning at SD Negeri 015/VIII Sungai Bengkal by 34%. ABSTRAKPenelitian ini bertujuan untuk menerapkan supervisi akademik dalam meningkatkan kompetensi pedagogik guru di SD Negeri 015/VIII Sungai Bengkal, Tebo Ilir, Tebo Provinsi Jambi semester ganjil tahun pelajaran 2015/2016. Metode penelitian ini adalah PTS (Penelitian Tindakan Sekolah). Kegiatan dalam penelitian ini terdiri atas tahapan perencanaan tindakan, pelaksanaan tindakan, observasi, dan refleksi. Teknik pengumpulan data menggunakan teknik obeservasi kelas. Instrumen observasi yang digunakan adalah alat penilaian kemampuan guru (APKG) berupa: 1) instrument penilaian kemampuan guru dalam mengembangkan silabus, 2) instrument penilaian kemampuan guru dalam menyusun rencana pembelajaran, 3) instrument penilaian kemampuan guru dalam pelaksanaan pembelajaran. Analisis data yang digunakan adalah teknik analisis deskriptif komparatif. Data kuantitatif yang diperoleh di deskripsikan dalam bentuk kata-kata atau penjelasan. Selanjutkan dilakukan komparasi data untuk memastikan ada tidaknya peningkatan kemampuan guru dalam menyusun perencanaan pembelajaran, peningkatan kemampuan guru dalam pelaksanaan. Hasil penelitian menunjukkan temuan bahwa supervisi akademik dapat: a) meningkakan kompetensi guru kelas VI dalam mengembangkan silabus di SD Negeri 015/VIII Sungai Bengkal sebesar 41%. b) meningkakan kemampuan guru kelas VI dalam menyusun rencana pembelajaran di SD Negeri 015/VIII Sungai Bengkal sebesar 39%. c) meningkakan kemampuan guru kelas VI dalam melaksanakan pembelajaran di SD Negeri 015/VIII Sungai Bengkal sebesar 34%.